(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Proteus mirabilis known for its motility, swimming and swarming motility and involvement in various infections, these two types of motility are important for tissue colonization, thus increase the pathogenicity of the bacteria. Materials and Methods: Twenty-one isolates from different clinical and animal sources belong to P. mirabilis were collected. The isolates identified using biochemical tests and the Vitek-2 compact system. Swimmer and swarmer cells media used to detect the effect of antibiotics, sodium azide and tannic acid. Results: Sodium azide inhibited swimming more effectively than swarming, with higher concentrations (0.1%) showing the greatest inhibition. Tannic acid also inhibited swimming and swarming, with greater effects on swimming cells, particularly from clinical isolates. Swarming motility, especially in animal-derived isolates, exhibited resistance to tannic acid. Additionally, the isolates showed varying resistance levels to antibiotics. Conclusions: This study demonstrated that, P. mirabilis exhibit different responses to antibiotics, sodium azide and tannic acid according to the type of cells whether it was swimmer or swarmer. Sodium azide and tannic acid inhibit swimming more than swarming cells. Antibiotics resistance patterns was differ according bacterial isolate and type of antibiotic. These finding could be used in future to enhance the activity of antibiotics especially those used to treat gram-negative bacterial infection.